Collision Analysis Of A Self Propelled Oil Barge (SPOB) Using Finite Element Method - Amalia Ika Wulandari; Rodlian Jamal Ikhwani; Suardi suardi suardi; Ratna Septati Yani; Andi Nadia Himaya; alamsyah alamsyah (Kapal: Jurnal Ilmu Pengetahuan dan Teknologi Kelautan, 2022)
Many ship accidents at sea cause oil spills that can pollute the sea especially ships carrying crude oil that experiences a collision, for example SPOB ship. SPOB is a ship that transports crude palm oil in Indonesia. Basically, the ship is collided with a jetty due to ocean waves hitting the hull as consequently the ship hull experienced a deformation. This research will be carried out on SPOB ships that experienced a collision with a jetty using two variations of the model, namely the jetty with fenders and without fenders with variation of speed. This study aims to determine the stress and deformation that occurs in the hull when experiencing a collision with a jetty. The method used in this study is a nonlinear method using Ansys. The results reveal that increasing speed of the ship is in line with stress and deformation values.